2004
DOI: 10.1007/s00198-004-1659-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-impact exercise on bone mineral density: a randomized controlled trial in premenopausal women

Abstract: This study indicates that high-impact exercise is effective in improving bone mineral density in the lumbar spine and upper femur in premenopausal women, and the results of the study may be generalized at the population level. This type of training may be an efficient, safe, and inexpensive way to prevent osteoporosis later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 33 publications
4
102
2
14
Order By: Relevance
“…Interventions incorporating ten to 100 jumps performed three to seven times weekly increases BMD in young adult women (47,(58)(59)(60)(61) (Fig. 3), demonstrating that this higherimpact loading elicits the overload necessary to stimulate bone formation.…”
Section: Longitudinal Unilateral Studiesmentioning
confidence: 93%
“…Interventions incorporating ten to 100 jumps performed three to seven times weekly increases BMD in young adult women (47,(58)(59)(60)(61) (Fig. 3), demonstrating that this higherimpact loading elicits the overload necessary to stimulate bone formation.…”
Section: Longitudinal Unilateral Studiesmentioning
confidence: 93%
“…Similarly, differences in BMD values have been shown in athletes participating in different sports [20,38,39]. These studies had also revealed increased BMD of both the hip and spine in women who added upper body resistance exercise to a routine of lower body resistance plus jump training, stressing that lower body training only influences BMD values at the hip, not the spine [21,24,37,40].…”
Section: Discussionmentioning
confidence: 79%
“…Mechanic load, induced in the course of exercise, is essential for adaptation of bone architecture in the place of the load (Vainionpää et al, 2005). That is the reason why movement is a significant element in prevention and treatment of osteoporosis.…”
Section: Exercise Medication and Bone Mineral Densitymentioning
confidence: 99%
“…Korpelainen et al (2006) didn't found the effect of long-term impact exercise on BMD at the radius and hip, while there was a positive effect on bone mineral content at the trochanter. High-impact loading exercise in osteopenic postmenopausal women was assessed by Chien et al (2000) and Vainionpää et al (2005). A 24-week program had a positive effect on the deceleration of the decline in BMD (Chien et al, 2000).…”
Section: Effect Of Exercise On Postmenopausal Bonementioning
confidence: 99%
See 1 more Smart Citation